Front Cover: The Dark Side of Photocatalysis: One Thousand Ways to Close the Cycle (Eur. J. Org. Chem. 19/2020). Issue 19 (13th May 2020) - Capaldo, Luca; Ravelli, Davide
Abstract : The Front Cover shows the Moon overlapped with a photocatalytic cycle, consisting of three different events: photocatalyst excitation, quenching, and restoration. Just as in the case of our satellite, photocatalytic processes have their own dark side as well. In particular, the latter step, namely the restoration, is often overlooked by synthesis practitioners and has been depicted out of focus, accordingly. Our review summarizes the different ways available to turn over the photocatalyst and classifies them according to the different species competent in this fundamental step. More information can be found in the Minireview by L. Capaldo and D. Ravelli et al.